Revisiting the early Christians on blessedness: In conversation with Willem S. Vorster’s work on the makarisms - Chris L. de Wet (Verbum et Ecclesia)
In this article, I aim to revisit and extend the work of Willem Vorster on blessedness in early Christianity, particularly his analysis of the makarisms in Matthew and Luke. Vorster’s insightful examination of Stoic and early Christian views on blessedness offers a framework for understanding the wisdom and apocalyptic themes within these beatitudes. His focus on the wisdom-oriented, ethical focus in Matthew and the apocalyptic, eschatological view in Luke provides a dual lens through which to view early Christian thought on happiness and virtue. While Vorster’s analysis is primarily concerned with 1st-century Christian thought, this article extends his framework into the 4th-century, exploring how early Christian thinkers further developed and adapted the makarisms. The reception of these teachings shifted, incorporating more structured and mystical interpretations influenced by the ascetic and monastic movements.